Peran Sekolah dalam Menanamkan Nilai-Nilai Akhlak pada Peserta Didik - Abdurrahman, Abdurrahman; Sada, Heru Juabdin; Bahri, Saiful; Seftiyani, Dewi (Attractive : Innovative Education Journal, 2022)
The purpose of the study was to find out how the role of schools in instilling moral values ??in students at SMP TirtayasaSukabumi Bandar Lampung. In this study, the researcher used descriptive qualitative research and the data collection tools used observation, interviews, and documentation. While the data analysis technique used interactive analysis technique, with the stages of data reduction, data presentation, then drawing conclusions. The results showed sta that the role of Tirtayasa Middle School in Bandar Lampung was very important in instilling moral values ??in students including the Principal and Educator Staff (Teachers) had been carried out well. The role of the school is 1) The role of the school as a mentor 2) The role of the school as a model (example) and 3) The role of the school as an advisor. Keywords: Akidah Akhlak Learning, Teacher Creativity, Teacher Role